Sex Differences in Discrimination of Shoal Size in the Guppy (Poecilia reticulata). (21st April 2016) - Lucon‐Xiccato, Tyrone; Dadda, Marco; Bisazza, Angelo
Abstract: For a diversity of species, differences in sexual and parental roles, along with differences in body morphology, often result in males and females having different diets, distinct predators and even different patterns of habitat use. As a consequence, the two sexes often face different environmental challenges and selection may favour the evolution of sex differences in cognition. We tested this prediction in the guppy ( Poecilia reticulata ). Under perceived hazard, individual guppies join the larger available social group, a behaviour that is thought to minimise predation risk. In this species, females are more frequently exposed to predation and more averse to predation risk; we therefore expected greater accuracy in shoal size discrimination in females. We compared the accuracy of male and female guppies in discriminating shoals of 4 and 6 conspecifics, which represents the upper limit of discrimination for this species. Overall, we found no sex differences in the accuracy of discriminating the two shoals. However, while females showed this ability at the beginning of the test, males began to select the larger group only after several minutes. In three control experiments, we found indications that this sex difference cannot be accounted for by differences in motivation or antipredator strategies between the two sexes, suggesting female guppies are more efficient at rapidly estimating shoal size.